A new approach in teacher education: Clinical practice - Kazu, Ibrahim Yaşar; Yenen, Emin Tamer (Ankara University, 2014)
In today's world, the development of communities, providing economic and technological progress is largely based on education. Considering the great importance of teachers to the quality of education, the implemented programs in the process of teacher education should be appropriate to the requirements of the new era. In this respect, the purpose of the study is to describe a new approach, clinical practice, in teacher education and to draw the conceptual frame of clinical practice in terms of its some specific features. Besides, encountered problems in faculty-school cooperation program and differences between traditional teaching practice in Turkey and clinical practice model have been defined in this study.
Ö?retmen yetiştirmede yeni bir yaklaşi{dotless}m: Klinik uygulama
Keywords: Clinical practice; Faculty-school cooperation; Teacher education programs; Teaching applications